2015
DOI: 10.1155/2015/529580
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Brain Tissue Oxygen Pressure-Guided Management in Moderate and Severe Traumatic Brain Injury Patients

Abstract: The purpose of this study was to compare the effect of PbtO2-guided therapy with traditional intracranial pressure- (ICP-) guided treatment on the management of cerebral variables, therapeutic interventions, survival rates, and neurological outcomes of moderate and severe traumatic brain injury (TBI) patients. From 2009 to 2010, TBI patients with a Glasgow coma scale <12 were recruited from 6 collaborative hospitals in northern Taiwan, excluding patients with severe systemic injuries, fixed and dilated pupils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…3 Several works published more recently have also explored the effect of P bt O 2 values on outcome after head injury. 10,17,19 Maloney-Wilensky published a systematic review in 2009 of 3 studies including 150 patients recovering from severe TBI. 19 It was concluded that brain hypoxia (P bt O 2 < 10 mm Hg) is associated with worse outcome after TBI and that treating patients to increase P bt O 2 may improve neurological outcome.…”
Section: The Literature Basis For Existing P Bt O 2 Treatment Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Several works published more recently have also explored the effect of P bt O 2 values on outcome after head injury. 10,17,19 Maloney-Wilensky published a systematic review in 2009 of 3 studies including 150 patients recovering from severe TBI. 19 It was concluded that brain hypoxia (P bt O 2 < 10 mm Hg) is associated with worse outcome after TBI and that treating patients to increase P bt O 2 may improve neurological outcome.…”
Section: The Literature Basis For Existing P Bt O 2 Treatment Thresholdsmentioning
confidence: 99%
“…28 In 2015 Lin et al published a prospective randomized study to compare the effect of P bt O 2 -guided therapy with traditional intracranial pressure-guided treatment on outcome in moderate and severe TBI patients. 17 They employed a P bt O 2 threshold of 20 mm Hg and concluded that the survival rate in the P bt O 2 -guided group was significantly increased at 3 and 6 months after injury, indicating that therapy directed by P bt O 2 monitoring is valuable for treatment in these patients. Eriksson et al published a study in 2012 and concluded that the first 72 hours of P bt O 2 monitoring predicts mortality similar to the analysis we present in this study.…”
Section: The Literature Basis For Existing P Bt O 2 Treatment Thresholdsmentioning
confidence: 99%
“…52 PbtO 2 has most robust evidence among all cerebral oxygenation-monitoring techniques, and multiple studies have demonstrated an association between low PbtO 2 and poor outcomes after TBI independent of ICP and CPP. 41,42,53,54 There is recent suggestion to routinely place probe in normal appearing brain, typically in the nondominant frontal lobe. 55 As with ICP therapy, a stepwise management approach is also used for PbtO 2 augmentation, which includes optimization of MAP/CPP, respiratory manipulations, and blood transfusions (in the setting of anemia).…”
Section: Brain Tissue Oxygen Partial Pressurementioning
confidence: 99%
“…At 3 months, the PbtO 2 goal directed therapy group had significantly more favorable outcome rates (64.3% compared to 39.6%) [ 87 ]. Other groups have similarly showed a decrease in mortality and improved 6-month GOS outcomes with the addition of goal directed PbtO 2 therapy over standard ICP/CPP therapy alone [ 88 , 89 ]. In aSAH, PbtO 2 monitoring has less of a role in predicting vasospasm or outcome [ 90 ].…”
Section: Pbto 2 Monitoringmentioning
confidence: 99%